Influence of Solvent Choice on Mitomycin C Loading and Stability in Electrospun Polyvinylidene Fluoride Nanofibers - Horakova, Jana; Jirkovec, Radek; Vrchovecka, Stanislava; Sidova, Andrea (ACS omega, 2025)
This study investigates the influence of solvent systems on incorporating the hydrophilic drug mitomycin C (MMC) into electrospun polyvinylidene fluoride (PVDF) nanofibers, with a focus on the often-overlooked issue of active substance degradation during storage. MMC was dissolved in either water or acetone and added to the electrospinning solution, followed by quantification of drug loading using liquid chromatography. Dissolution of MMC in water resulted in poor drug loading efficiency. In contrast, acetone led to significantly higher incorporation, with 50.66% loading for PVDF containing 0.01% MMC and 26.63% for PVDF with 0.1% MMC. However, storage at 4 °C over 21 days resulted in a substantial decline in MMC content, indicating challenges in long-term stability. In vitro testing using mouse fibroblasts revealed no cytotoxic effects of the nanofibrous layers and demonstrated a reduction in fibroblast proliferation in MMC-loaded samples compared to pure PVDF controls. These findings highlight the importance of solvent selection for effective drug incorporation and point to the potential of PVDF-based nanofibers for antifibrotic applications.